2021
DOI: 10.3389/fmicb.2021.738596
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Resistance and Oxidation Mechanisms of Sb-Oxidizing Bacteria for the Bioremediation of Sb(III) Pollution

Abstract: Antimony (Sb) is a priority pollutant in many countries and regions due to its chronic toxicity and potential carcinogenicity. Elevated concentrations of Sb in the environmental originating from mining and other anthropogenic sources are of particular global concern, so the prevention and control of the source of pollution and environment remediation are urgent. It is widely accepted that indigenous microbes play an important role in Sb speciation, mobility, bioavailability, and fate in the natural environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 156 publications
0
6
0
Order By: Relevance
“…This is an antimony-resistance detoxification mechanism in SbRM and becomes predominant in stress conditions. However, the excess Sb­(III) accumulation might disrupt the redox balance and lead an oxidation of Sb­(III) . Therefore, the Sb­(V) loading should be controlled to avoid cytoplasm Sb­(V) reduction lead the route and make the dissimilatory in main route.…”
Section: Resultsmentioning
confidence: 99%
“…This is an antimony-resistance detoxification mechanism in SbRM and becomes predominant in stress conditions. However, the excess Sb­(III) accumulation might disrupt the redox balance and lead an oxidation of Sb­(III) . Therefore, the Sb­(V) loading should be controlled to avoid cytoplasm Sb­(V) reduction lead the route and make the dissimilatory in main route.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Sb(III) oxidation has been frequently reported in this T h i s c o n t e n t i s region, 20,21 which can reduce the toxicity of Sb given that Sb(III) is more toxic than Sb(V). 22,23 Our previous studies indicated diverse diazotrophic communities in this region. 24,25 Therefore, the investigation of Sb-dependent BNF has important environmental implications for improving N fertilizer efficiency and managing Sb toxicity in the environment.…”
Section: ■ Introductionmentioning
confidence: 82%
“…The giant Sb metallogenic belt in South China (South China Sb belt) is the major Sb deposit in China, with >500 Sb deposits within the transition zone between the Yangtze river and Cathaysia blocks in southern China. The extensive Sb mining activities cause severe soil, sediment, and water contamination in this region. Given the oligotrophic geochemical conditions and high concentrations of Sb in this region, , it is fair to propose that Sb-dependent BNF may be widespread among these Sb-contaminated regions. Indeed, Sb­(III) oxidation has been frequently reported in this region, , which can reduce the toxicity of Sb given that Sb­(III) is more toxic than Sb­(V). , Our previous studies indicated diverse diazotrophic communities in this region. , Therefore, the investigation of Sb-dependent BNF has important environmental implications for improving N fertilizer efficiency and managing Sb toxicity in the environment.…”
Section: Introductionmentioning
confidence: 88%
“…Sb's toxicity extends with to plants, animals, and humans, with excess intake linked to serious health issues including cancers, cardiovascular and liver disease as well as respiratory disorders [4]. In plants, Sb toxicity manifests as inhibited growth and development, evidenced by alterations in root morphology and reduced root system development [5][6][7]. Kabata and Pendias [8] suggest that Sb levels exceeding 5-10 mg kg −1 Sb in plant tissues can be detrimental, significantly reducing seed germination, shoot and root growth, and ultimately impacting plants growth and production.…”
Section: Introductionmentioning
confidence: 99%